Perbedaan Perkembangan Motorik Halus Pada Bayi 0-6 Bulan Yang diberikan ASI Eksklusif dan Non ASI Eksklusif - Nabila, Faza (IJMT : Indonesian Journal of Midwifery Today, 2024)
ABSTRACT Exclusive breastfeeding is the provision of full breastfeeding for the first 6 months without giving other food or drink to the baby. The content of breast milk including AA and DHA is useful in accelerating myelination. Breast milk has a beneficial effect on fine motor development. The purpose of this study was to determine the differences in fine motor development of infants aged 0-6 months who were given exclusive breastfeeding and non-exclusive breastfeeding. The study used a cross-sectional analytical method. The population was all infants aged 0-6 in the Candi Community Health Center area in February-March. Sampling using consecutive sampling technique. The sample size was 46 respondents. The independent variables were exclusive breastfeeding and non-exclusive breastfeeding. The dependent variable was the development of the infant's gross motor skills. The instrument used an interview sheet and Denver II. Data sources from interviews and examinations. Data analysis used the Fisher test. The results of the study from 46 respondents, more than half of the infants (65.2%) were given non-exclusive breastfeeding, the development of fine motor skills was mostly normal (78.3%). The results of the Fisher test p = 0.130. So p> α, meaning there is no difference in breastfeeding with the development of infants' fine motor skills. The conclusion of this study, most respondents have normal fine motor development, most are given non-exclusive breastfeeding and there is no difference in fine motor development of babies aged 0-6 months who are given exclusive breastfeeding and non-exclusive breastfeeding. However, giving exclusive breastfeeding for the first 6 months is important to prioritize because of the advantages it has.